Amaranthus tricolor: A Nutrient-Dense Functional Food with Promising Therapeutic Potential (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Amaranthus tricolor, or red amaranth, is a nutritionally dense leafy vegetable with broad medicinal and dietary applications, commonly consumed in tropical and subtropical regions. Traditionally, it has been used in Siddha and Ayurveda to address a range of conditions including diarrhea, dysentery, bronchitis, and hemorrhagic ailments. Recent studies emphasize its diverse pharmacological potential, showcasing its antimicrobial, hepatoprotective, anti-diarrheal, neuroprotective, cardioprotective, anti-melanin, anthelmintic, antibacterial, anticancer, anti-nociceptive, and anti-inflammatory activities. These therapeutic properties are largely attributed to the plant’s rich profile of phytochemicals, including phenolics, flavonoids, alkaloids, betacyanins, and amaranthine. In terms of nutritional value, A. tricolor is an exceptional source of essential nutrients like vitamins A and C, carotenoids, calcium, iron, and several key minerals, presenting an advantageous profile over common greens such as lettuce and spinach. The plant’s antioxidant activity, critical for neutralizing reactive oxygen species (ROS), has implications for reducing oxidative stress and supporting the prevention of aging and chronic diseases. Additionally, research indicates that salt-stressed A. tricolor plants exhibit elevated antioxidant levels, suggesting a resilience that allows cultivation under diverse environmental conditions. Despite these promising attributes, specific bioactive compounds contributing to its extensive health benefits remain underexplored. This study aims to consolidate findings on the nutritional composition, antioxidant potential, and extensive pharmacological activities of A. tricolor, underscoring its value as an economically viable, nutrient-dense crop with considerable therapeutic applications and encouraging further research.